THE ROLE OF THE COMMUNICATIVE APPROACH IN ENGLISH LANGUAGE TEACHING: THEORY, PRACTICE AND CHALLENGES - Sadritdinova Y.F.; Gaybullayeva X.M. (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This paper provides an expanded analysis of the communicative approach (CA) in English language teaching (ELT), exploring its theoretical background, classroom applications, pedagogical principles, and methodological challenges. The study discusses communicative competence, task-based learning, authentic input, interaction patterns, and the role of affective factors. It examines how digital technologies, collaborative tasks, and socio-cultural contexts influence communicative development. Findings show that CA enhances fluency, accuracy in meaningful contexts, learner autonomy, motivation, and higher-order thinking. Recommendations are provided for teachers and curriculum developers to integrate CA more effectively in modern classrooms.